2010
DOI: 10.1104/pp.109.149989
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofdrr1, an Alkamide-Resistant Mutant of Arabidopsis, Reveals an Important Role for Small Lipid Amides in Lateral Root Development and Plant Senescence

Abstract: Alkamides belong to a class of small lipid signals of wide distribution in plants, which are structurally related to the bacterial quorum-sensing signals N-acyl-L-homoserine lactones. Arabidopsis (Arabidopsis thaliana) seedlings display a number of root developmental responses to alkamides, including primary root growth inhibition and greater formation of lateral roots. To gain insight into the regulatory mechanisms by which these compounds alter plant development, we performed a mutant screen for identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…Alteration of root development by AHLs or plant growth-promoting rhizobacteria involves jasmonate, ethylene, and salicylic acid signaling pathways (Méndez-Bravo et al, 2010;Morquecho-Contreras et al, 2010;Shi et al, 2010). Here, we found that 3-O-C10-HL still retained the partial ability to promote adventitious root formation even in the presence of the auxin transport inhibitor NPA, indicating that auxin-independent signaling should not be excluded and may participate in 3-O-C10-HL-induced adventitious root formation.…”
Section: Branched Chain Structures Of Ahls Affect Root Auxin Polar Trmentioning
confidence: 63%
See 4 more Smart Citations
“…Alteration of root development by AHLs or plant growth-promoting rhizobacteria involves jasmonate, ethylene, and salicylic acid signaling pathways (Méndez-Bravo et al, 2010;Morquecho-Contreras et al, 2010;Shi et al, 2010). Here, we found that 3-O-C10-HL still retained the partial ability to promote adventitious root formation even in the presence of the auxin transport inhibitor NPA, indicating that auxin-independent signaling should not be excluded and may participate in 3-O-C10-HL-induced adventitious root formation.…”
Section: Branched Chain Structures Of Ahls Affect Root Auxin Polar Trmentioning
confidence: 63%
“…Previous studies showed that modulating Arabidopsis primary and lateral root formation by some AHLs or alkamide, particularly those AHLs with an unmodified branched chain, is independent of auxin signaling (Ortíz-Castro et al, 2008;Méndez-Bravo et al, 2010;Morquecho-Contreras et al, 2010). For example, C10-HL treatment was unable to enhance GUS activity in Arabidopsis transgenic seedlings harboring the auxinresponse DR5:uidA gene construct (Ortíz-Castro et al, 2008).…”
Section: Branched Chain Structures Of Ahls Affect Root Auxin Polar Trmentioning
confidence: 99%
See 3 more Smart Citations